CRUSTOSE CORALLINE ALGAL PAVEMENTS FROM LATE EOCENE COLLI BERICI OF NORTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
The Eocene from the Prealpine region records the first phase of the crustose coralline algae flourishing in the Cenozoic. These algae are very frequent in the Marne di Priabona Formation (Late Eocene). This palaeoecological research involves ourcrop at Barbarano Vicentino(Vicenza) in the Colli Berici which is well known for its Paleogene stratigraphy. The coralline unit consists of a floatstone bank 6 m thick with rhodoliths and laminar crusts; it lies between macroforaminifer dominated limestone (Middle Eocene) and coral-algal  massive limestone (earliest Oligocene). Lithothamnion, Sporolithon,  Mesophyllum, and some Lithoporella and Spongites have been recognized. Bryozoans, large foraminifera, bivalves, echinoids, serpulids, benthic and rare planktic forams also occur. The large  foraminifera are represented  by Nummulites, Discocyclina, Operculina, Asterocyclina, Spiroclypeus, Gypsina, Pellatispira, Biplanispira.The coralline association is dominated by Lithothamnion. A lower and an upper facies have been recognized. Small rhodoliths made up of thin crusts  around a large core,  or several encrusting stages characterise the lower part of the unit; big rhodoliths (4-10 cm in size) with a complex inner structure  and several thin delicate laminar crusts occur in the upper part; groups of laminar crusts, parallel to the depositional surface, are frequent too. Bioclastic lenses rich in large foraminifera and bryozoans, without rhodoliths, occur in the lower part of the unit. The Priabonian algal community built a "Crustose Pavement" on the open shelf (shallow circalittoral) below the wave base at 50-100 m in depth, occasionally influenced by storms. The morphology of the thalli suggests a decrease in hydrodynamic energy or an increase in depth from the bottom to the top of the unit.
Keywords: Coraliine Algae; Palaeoecology; Late Eocene; Veneto; Northern Italy.